Mengelola Stres Belajar Siswa Dengan Mengefektivitas Penggunaan Video Relaksasi Bagi Siswa Kelas VII A di SMP Negeri 4 Ajangale - Agussalim, Agussalim (Universitas Negeri Makassar, 2018)
This study examines the effectiveness of the use of relaxation video to manage students' stress learning in SMP Negeri 4 Ajangale. This study used a quantitative approach with pre-experimental designs on 30 subjects who were randomly picked and were students of CLASS VII A in SMP Negeri 4 Ajangale. Data collection using stress scale learning instrument. Data analysis using descriptive statistical analysis and inferential statistical analysis, namely t-test. The results of the study showed that: (1) The level of stress of learning in SMP Negeri 4 Ajangale, before treatment in the form of relaxation exercise using relaxation video is in high category but after being treated in the form of relaxation exercise using relaxation video, stress level of student learning can be managed and in very low category. (2) The use of effective relaxation video to manage students' stress in SMP Negeri 4 Ajangale